An assessment of a proposed ETS in Australia by using the MONASH-Green model. (September 2017) - Nong, Duy; Meng, Sam; Siriwardana, Mahinda
Abstract: Using the MONASH-Green model and a database containing detailed energy sectors, this paper evaluates the effects of a proposed emissions trading scheme on the Australian economy and the emissions levels. The simulation results indicate that the price of carbon permits has to increase from A$4.1 per tonne in 2015 through A$13.1 per tonne in 2020 to A$41.3 per tonne in 2030 to achieve a target of 28% below the 2005 level in 2030. The main buyers of permits would be the agricultural sector, black-coal electricity sector and brown-coal electricity sector. Compared to the business-as-usual scenario, Australia's GDP is projected to be 0.85% lower in 2020 and 1.6% lower in 2030. Household welfare, measured in terms of equivalent variations, will increase due to compensations provided by the government. The results also lend strong support towards the transition to renewable energy. The stylised model was adapted to inform the results of the full model. Highlights: The paper evaluates the effects of a proposed ETS in Australia by using the MONASH-Green model. Emissions permit price increases from A$4.1 in 2015 to A$41.3 in 2030. The Australian economy experiences a mild contraction after the ETS. The ETS can facilitate Australia to transit to a low carbon economy.